Handbook of employee selection - Farr, James L.; Tippins, Nancy Thomas, 1950- (New York : Routledge, 2010)
The Handbook of Employee Selection provides a comprehensive review of a) contemporary personnel selection instruments, including the technical methodology for their development and evaluation of their effectiveness, b) the organizational systems necessary for the effective and efficient use of personnel selection methods as part of organizations human resource management approach, and c) the societal and organizational factors that provide the context within which personnel selection is nested. The Handbook will include descriptions of specific examples of personnel selection procedures that have had major impact on the development of personnel selection function within organizations, as well as discussions of current and future trends in employee selection around the world.
Includes bibliographical references and indexes.
Keywords: Employee selection; Employee selection -- Handbooks, manuals, etc